2020
DOI: 10.1155/2020/7509612
|View full text |Cite
|
Sign up to set email alerts
|

Tetrastigma hemsleyanum Vine Flavone Ameliorates Glutamic Acid-Induced Neurotoxicity via MAPK Pathways

Abstract: Glutamic acid (Glu) is a worldwide flavor enhancer with various positive effects. However, Glu-induced neurotoxicity has been reported less. Tetrastigma hemsleyanum (TH), a rare herbal plant in China, possesses high medicinal value. More studies paid attention to tuber of TH whereas vine part (THV) attracts fewer focus. In this study, we extracted and purified flavones from THV (THVF), and UPLC-TOF/MS showed THVF was consisted of 3-caffeoylquinic acid, 5-caffeoylquinic acid, quercetin-3-O-rutinoside, and kaemp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…As one of the basic amino acids, glutamate is involved in many crucial chemical reactions in the body and plays an important role in protein metabolism in organisms [ 28 ]. Glutamate was shown to effectively promote the proliferation of hair papilla cells, while glutamate at high concentrations caused calcium overload that interfered with mitochondrial respiratory chain function, thereby inhibiting cystine uptake and causing GSH deprivation and ROS accumulation, ultimately leading to cell necrosis or apoptosis [ 29 , 30 ]. The glutamate content decreased in the Ni 2+ -24 h group but increased in the 48 h group, indicating that glutamate might not have adverse effects on cells at low concentrations but might cause mitochondrial dysfunction, affecting ATP synthesis, causing oxidative damage and eventually leading to cell apoptosis or death at high concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…As one of the basic amino acids, glutamate is involved in many crucial chemical reactions in the body and plays an important role in protein metabolism in organisms [ 28 ]. Glutamate was shown to effectively promote the proliferation of hair papilla cells, while glutamate at high concentrations caused calcium overload that interfered with mitochondrial respiratory chain function, thereby inhibiting cystine uptake and causing GSH deprivation and ROS accumulation, ultimately leading to cell necrosis or apoptosis [ 29 , 30 ]. The glutamate content decreased in the Ni 2+ -24 h group but increased in the 48 h group, indicating that glutamate might not have adverse effects on cells at low concentrations but might cause mitochondrial dysfunction, affecting ATP synthesis, causing oxidative damage and eventually leading to cell apoptosis or death at high concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…Thus 3-O-caffeoylquinic acid and caffeic acid treatment improved memory in the mouse model of Aβ accumulation by the inhibition of oxidative stress, inflammation and apoptosis through the p38 mitogen-activated protein kinase (MAPK) signaling pathway [ 35 , 36 ]. Similarly, Chu et al [ 37 ] observed that a flavone-rich extract of Tetrastigma hemsleyanum whose major components were 3-caffeoylquinic acid, 5-caffeoylquinic acid and quercetin-3-O-rutinoside, and kaempferol-3-O-rutinoside could attenuate glutamate-induced toxicity in PC12 cells and C. elegans . This extract lessened genotoxicity, relieved oxidative stress and recovered mitochondrial functions in PC12 cells via the MAPK pathway by suppressing the over-phosphorylation of ERK and p38.…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, efflux of glutamic acid and decreased intracellular glutamic acid could reduce GSH synthesis as well. GSH depletion leads to the accumulation of ROS and the consumption of SOD enzyme [ 12 , 27 , 33 , 39 ]. Our experimental results suggested that the intracellular Ca 2+ level of HT22 cells was significantly increased and the activity of Ca 2+ -ATPase was significantly inhibited after aconitine stimulation.…”
Section: Discussionmentioning
confidence: 99%